A Vermetid Bioconstruction at the Adriatic Coast of Apulia (Italy) - Maria Mercurio; Isabella Coccia; Manuel Marra; Tamara Lazic; Giuseppe Corriero; Maria Flavia Gravina (Diversity)
This study presents the first comprehensive data on a vermetid formation along the Apulian coast of the Adriatic Sea, representing one of the northernmost records in the Mediterranean. Surveys along the Brindisi coastline employed visual inspection to map the bioconstruction’s distribution and extension. Detailed data on the bioconstruction inner and the outer edge length, thickness, width, slope and topographic complexity were collected at three selected sites. Moreover, photographic replicates were used to assess shell aperture density and diameters of Dendropoma sp. Associated fauna was studied using two quantitative sampling squares in each transect. The results showed that the vermetid bioconstruction consisted of a thin, encrusted monolayer (thickness < 1.5 cm) that extended for 3.273 linear kilometers, covering 17.23% of the investigated area; it had an average width of 0.5 m, with a mean density of Dendropoma sp. at 2.52 ind/cm2. The associated fauna was composed of 47 taxa dominated by crustaceans, mollusks and annelids. Species richness was correlated with the bioconstruction’s thickness and complexity. These findings underline the ecological importance of vermetid bioconstructions as biodiversity hotspots. The lack of massive mortality events along the Apulian coast, in contrast to other Mediterranean vermetid bioconstructions, underscores the necessity for targeted conservation measures.